2017
DOI: 10.1007/s12020-017-1267-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing pre-therapeutic 124I and 131I uptake tests with intra-therapeutic 131I uptake in benign thyroid disorders

Abstract: I RAIU tests represent a feasible alternative to standard I RAIU tests. The additional benefits ofI-PET/CT (e.g., functional topography, inclusion of retrosternal areas, possibility to enable fusion imaging) may thus increase the scope of this technology in benign thyroid disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Similar pretherapeutic tracer studies have been reported in hyperthyroid cats 52‐54 . However, when pretherapeutic 131 I uptakes are compared to those measured after administration of therapeutic doses of 131 I, the 131 I uptake values do not always agree 49,54‐57 . One possible reason for this discrepancy is that 131 I therapy might induce early radiobiological effects, which changes the 131 I uptake and limits the usefulness of pretherapeutic dosimetry 49,55‐57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar pretherapeutic tracer studies have been reported in hyperthyroid cats 52‐54 . However, when pretherapeutic 131 I uptakes are compared to those measured after administration of therapeutic doses of 131 I, the 131 I uptake values do not always agree 49,54‐57 . One possible reason for this discrepancy is that 131 I therapy might induce early radiobiological effects, which changes the 131 I uptake and limits the usefulness of pretherapeutic dosimetry 49,55‐57 .…”
Section: Discussionmentioning
confidence: 99%
“…52 , 53 , 54 However, when pretherapeutic 131 I uptakes are compared to those measured after administration of therapeutic doses of 131 I, the 131 I uptake values do not always agree. 49 , 54 , 55 , 56 , 57 One possible reason for this discrepancy is that 131 I therapy might induce early radiobiological effects, which changes the 131 I uptake and limits the usefulness of pretherapeutic dosimetry. 49 , 55 , 56 , 57 To avoid these discrepancies, some investigators have proposed doing a 2‐step 131 I treatment in human patients, as needed based on 131 I uptakes measured after administration of an initial 131 I therapy dose.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the fact that incorrectly measured values are generated by incorrect tilting of the phantoms or of the patient, the distance of 30 cm between measuring object and probe is extremely susceptible to errors. The mentioned previous study showed that these measurement errors can easily be relativized by increasing the distance [31].…”
Section: Discussionmentioning
confidence: 96%
“…We noticed measurement deviations due to patient positioning. Overflexion of the head leads to less, and overinflexion to more distance [31]. Regardless of the fact that incorrectly measured values are generated by incorrect tilting of the phantoms or of the patient, the distance of 30 cm between measuring object and probe is extremely susceptible to errors.…”
Section: Discussionmentioning
confidence: 99%
“…Takođe, značajan argument pobornika pristupa fiksne doze predstavlja i nepreciznost izračunate doze apsorbovanog zračenja, koja otežava korelaciju doza-efekat (6,22,33). Stvarna doza apsorbovanog zračenja koju prime tireociti nakon primjene izračunate doze aktivnosti može da se razlikuje od namjeravane (propisane) doze, što može biti posljedica primjene pojednostavljenih protokola za procjenu retencije radioaktivnog joda u štitastoj žlijezdi (17,34,35), razlika u poluvremenu eliminacije 131 I prije i tokom terapije (36,37), zatim smanjenja volumena štitaste žlijezde u toku terapije (38,39), razlika u veličini tireoidih folikula od koje zavisi izloženost tireocita zračenju (40), kao i primjena standardizovanih modela (fantoma) za procjenu E vrijednosti (33,41). Osim toga i brojni drugi faktori mogu da utiču na ishod terapije, poput individualne radiosenzitivnosti pacijenata i primjene antitireoidnih lijekova(42), što je, takođe, otežavajući faktor uspostavljanju korelacije između apsorbovane doze zračenja i efekta terapije (6).…”
Section: Doziranje Radioaktivnog Jodaunclassified